Acute Fatty Liver in Pregnancy - Duangrat, TithigenYa; Pongprasopchai, SuPot; Lekprasert, ViriYa; ArronPruksakul, Naiyana (Siriraj Medical Journal, 2002)
We report woman with a 36 week twin pregnancy who presented with labor pains 8 hours prior to hospitalization. Jaundice was found on clinical examination in the out patient department. After admission for investigation, laboratory tests which demonstrated abnormal bleeding rapidly worsened and the condition of the fetus was worsened. Emergency caesarian section was performed while resuscitating the patient. The twins were delivered with good outcome but their mother’s condition worsened and she expired from sepsis on the 32nd day after admission. The differential diagnosis of jaundice in the third trimester pregnancy, treatment, optimization for operation and outcome of acute fatty liver of pregnancy are discussed. Acute fatty liver in pregnancy is a rare but fatal disease for pregnant woman.